Hubungan Keteraturan Ante Natal Care dengan Kejadian Pre-eklamsia dan Eklamsia di Wilayah Kerja Puskesmas Peterongan - Agustina, Cici Yunitasari; Praningsih, Supriliyah; Lestari, Rini Hayu (Jurnal Kesehatan Komunitas Indonesia, 2016)
The mother's mortality rate is one of the important indicator in scoring the level of health in a country. It is very high in Indonesia. Pre-eclampsia/ eclampsia which indicate the high blood pressure during pregnancy become one of the factor that lead this mortality rate. The Regular examination of Antenatal care (ANC) is one of the way to avoid the pre-eclampsia/ eclampsia. The purpose of study is to know the correlation of ANC regularity with the occurance of pre-eclampsia/ eclampsia in Puskesmas Peterongan. The design of the study was analytic correlational with retrospective approach. The independent variable was the ANC regularity and dependent variable was pre-eclampsia/ eclampsia. The populations were all pregnancy mothers (gestational age ≥ 36 weeks) with pre-eclampsia/ eclampsia and the lateboring mothers with pre-eclampsia/ eclampsia at Puskesmas Peterongan in 2017 as many as 41 people. Samples used total sampling as many as 41 respondents. Statistical test used spearman rank. Most of the respondents (56,1%) was not regularly to do ANC at Puskesmas Peterongan in 2017 as many as 23 respondents. Most of the respondents (68,3%) had mild pre-eclampsia at Puskesmas Peterongan in 2017 as many as 28 respondents. The result of statistical test gained significant score as much as 0,235 > 0,05 which showed the was no correlation between ANC regularity with the occurance of pre-eclampsia/ eclampsia in Puskesmas Peterongan. The visite of ANC could early detect the pre-eclampsia/ eclampsia. The mother hoped regularly to do the ANC to avoid complication during pregnancy and decrease maternal mortality of mother.